Influence of plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi on growth and yield of strawberry (Fragaria x ananassa Duchesne) - Samsurrijal, Nur Laili (2019)
Strawberry is one of the main crops in Cameron Highlands, Pahang, Malaysia, which contribute significantly to the economy of local people. It was being grown all year round in substrate media under fertigation system. This system consumes high chemical fertilizer that can increase input cost and may lead to environmental pollution. The application of plant growth-promoting rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF) could be the solution for better plant performance with lesser chemical input. The following studies aimed to 1) characterize the growth-promoting traits of bacteria isolated from strawberry roots, 2) determine the effects of PGPR and AMF on growth and fruit quality and 3) observe the bacterial colonization on plant roots under controlled condition. In Study 1, bacterial isolates obtained from rhizosphere of three strawberry cultivars (Camarosa, Festival and Chandler) grown in Cameron Highlands, were differentiated based on phenotypic characterization, evaluated for various beneficial traits and identified using molecular technique. The selected bacterial isolates were then evaluated for plant growth promoting performance. A fertigation study was conducted with five treatments consisting of four bacterial isolates and non-inoculated which was served as control. All plants were applied with 70% nutrient strength. The study was arranged in randomized complete block design (RCBD) with three replications (three plantlets per replication). In Study 2 the following treatments were; 1) control – non-inoculated (100% strength); 2) control - uninoculated (70% strength); 3) G. mosseae (70% strength); 4) M. oxydans (70% strength); and 5) dual inoculation (70% strength). Plant growth, berry yield production, fruit quality and plant root colonization were determined. In Study 3, colonization of bacteria on plant roots was observed using Scanning Electron Microscope (SEM). Results in Study 1 showed a total of 80 PGPR were isolated from different strawberry cultivars. Fifty isolates were positive for biological N2-fixation and 26 showed potassium solubilizing activity. Five of the isolates showed phosphate solubilizing activity and the solubilizing efficiency ranged from 13.2 to 42.3%. Only few produced hydrolyzing enzyme. Most isolates produced phytohormone which ranged from 1.6 to 42.4 µg mL⁻¹. Four of the selected bacteria were identified as Microbacterium oxydans (STUPM01), Bacillus cereus (STUPM12), Leclercia adecarboxylata (STUPM20) and Pseudomonas umsongensis (STUPM 25). Plants inoculated with M. oxydans showed better root development and highest in leaf surface area and leaf dry weight. In Study 2, microbial treatments enhanced root dry weight compared to non-inoculated control (70% strength). M. oxydans inoculation resulted in higher shoot and root dry weights than both controls. Leaf surface area also increased 13% - 21% with G. mosseae and M. oxydans, respectively. Microbial treatments resulted in increment of berry yield from 11% - 20% compared to non- inoculated control of the same nutrient strength. The number of fruits produced increased to 15% in M. oxydans treatment. Higher average weight of fruits was obtained in plant treated with M. oxydans and dual inoculation. Microbial treatments enhanced the amount of sugars (glucose, sucrose, fructose) as well organic acids (ascorbic, malic, citric) in the strawberry fruit. Mycorrhizal roots harvested were observed with the presence of vesicles and hyphae in the roots. In Study 3, the colonization of M. oxydans on strawberry roots was visually observed with SEM technique and bacterial cells were found to colonize the roots. These studies showed that beneficial PGPR were successfully isolated from strawberry roots, and growth and yield of strawberry was significantly increased when inoculated with PGPR and AMF.